A Concept of Chatushka Methodology in Charak Samhita-A Review - Singh, Naval; Gupta, Nisha (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda has the distinction of being the "oldest medical system and the oldest and most comprehensive spiritual teachings in the world". Ayurveda is based on the principle of maintaining a balance between the interrelated relationships within the body and mind. The Brihatrayee-Charaka Samhita, Susruta Samhita and Ashtanga Hridaya are the three primary authoritative works in Ayurveda. There are 8 Sthanas in the Charaka Samhita, 5 Sthanas in the Susruta Samhita and 5 Sthanas in the Astanga Hridaya. The 120 Chapters of the Charaka Samhita are divided into 8 Sthanas. Sutrasthana is one among them, which is placed first in Charaka Samhita. The foundational theory of Ayurveda and its technique for life are extensively detailed in Sutrasthana. Sutrasthana from the Charaka Samhita known as the Shira. 30 chapters of Sutrasthana are categorized under seven groups of four chapters known as Sapta Chatushka. Specifically, Aushadha, Swastha, Nirdesh, Kalpana, Roga, Yojana and Annapana Chatushka. remaining two chapters are the collection of the information termed as the Sangraha Dwaya. Here, an attempt is made to teach the Chatushka process in Sutrasthana in a methodical and detailed manner that provides the foundational information for treatment. This is one of Charaka Samhita’s unique qualities.